The Theory That Won't Go Away: An Updated Review of the Role Hypnosis Plays in Mind Control - Eichel, Steve K. D. (International journal of coercion, abuse and manipulation IJCS, 2022)
Over the years, hypnosis has been a central feature in descriptions of the process of behavior and attitude change that occurs in high-demand groups (HDGs, or cults). Cult specialist and mental-health counselor Steven Hassan (1989, 2000, 2014) has talked and written extensively about this process. In August 2000, Dr. Arthur Dole chaired a symposium at the annual meeting of the American Psychological Association (APA) entitled Can Hypnosis Explain Cult Conversion? Evidence From Science and Practice, which included a number of experts in the field (Dole et. al., 2000). In contrast to the premise suggested by these references, Spanish psychologist Jose Fernández Aguado (2015), in a provocative article entitled “Psychological Manipulation, Hypnosis, and Suggestion,” questioned the ability of hypnosis to induce people to engage in behaviors in ways they would not otherwise execute “out of” hypnosis.